Agricultural Sector Policy Note for Bosnia and Herzegovina : Trade and Integration Policy Notes - World Bank (Washington, DC, 2013)
The agricultural season in Bosnia and Herzegovina (BH) begins earlier than in most European countries, shipping costs are relatively low, and land and labor prices are more favorable than in other southern European countries. As a result, the country's agriculture sector should be well positioned to compete on the export markets. With 20.6 percent of all employed in BH, agriculture remains an important sector for employment, despite a decline in the working-age population in rural areas. Additionally, it will be important for BH to develop well-functioning land institutions, so that the land market can operate more efficiently and thus enable business development. Finally, BH should integrate climate change adaptation and environmental sustainability into agricultural policies, programs, and investments. To succeed in agriculture, producers and governments will have to adapt, and the way to start is to focus on reducing agriculture's vulnerability to current climate variability.